Determinants of anemia in pregnant women: Nutrition status, birth interval, parity - Putri, Anggun Amanda; Rahmawati, Alfiah (Journal of Midwifery and Nursing, 2025)
Anemia in pregnancy is a serious health problem that can adversely affect both mother and fetus. The prevalence of anemia among pregnant women in Indonesia increased from 37.1% in 2013 to 48.9% in 2018, well above the national target of 28%. Factors such as nutritional status, birth spacing, and parity are known to contribute to the incidence of anemia. This study aims to analyze the effect of nutritional status, birth spacing, and parity on anemia in pregnant women based on a literature review. The method used was literature review from electronic sources such as Google Scholar, PubMed, BioMed Central (BMC), and SINTA with inclusion criteria of articles published between 2019-2024. The results showed that poor nutritional status increased the risk of anemia up to 6 times, pregnancy spacing <2 years related to decreased hemoglobin levels, and high parity increased the risk of anemia due to lack of iron recovery. In conclusion, nutritional status, pregnancy spacing, and parity affect the incidence of anemia in pregnant women.